Impact of water origin and composition on the desalting of fully salt-cured cod ... - Dargentolle, Cecile; Dupont, Maxime; Sveinsdóttir, Hildur Inga; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
Salt-cured cod is a product popular in Mediterranean countries like Portugal and Spain. Usually, consumers desalt the product in their kitchen, or it is desalted by the producers in the factory. However, a large portion of those products is produced in Iceland and sold fully salt-cured to buyers in the Mediterranean countries. In recent years, market requirements have changed towards more demand for desalted products. Huge amount of water is needed for desalting, and water in Iceland is generally cheaper than in Mediterranean countries. In order to examine if desalting is a viable option for the producers of fully salt-cured cod in Iceland, composition and effect of water used for desalting in Iceland, Spain and Portugal on end-product quality was compared. Brine injected products were desalted with water from three locations in Iceland and one in Spain. Pickle salted products were desalted with water from two locations in Iceland and one in Portugal. Mineral composition and pH of water from the different ...